Determinan Kinerja Pegawai melalui Kepuasaan Kerja Pada Puskesmas Di Kota Padang - Yuli Angraini; Fasridon Fasridon (Politeknik Kampar, 2024)
This study aims to analyze and prove the influence of Transformational Leadership Style and Work Environment on Employee Performance through Job Satisfaction at the Ambacang Kuranji Health Center. This study uses the SEM or Smart PLS 3 analysis tool. The results of this study prove that the most dominant opportunity is the Transformational Leadership Style on Job Satisfaction and Job Satisfaction on Employee Performance at the Ambacang Kuranji Health Center